Long-term insights into marine turtle sightings, strandings and captures around the UK and Ireland (1910–2018). (19th September 2020) - Botterell, Zara L. R.; Penrose, Rod; Witt, Matthew J.; Godley, Brendan J.
Abstract: With over a century of records, we present a detailed analysis of the spatial and temporal occurrence of marine turtle sightings and strandings in the UK and Ireland between 1910 and 2018. Records of hard-shell turtles, including loggerhead turtles ( Caretta caretta, N = 240) and Kemp's ridley turtles ( Lepidochelys kempii, N = 61), have significantly increased over time. However, in the most recent years there has been a notable decrease in records. The majority of records of hard-shell turtles were juveniles and occurred in the boreal winter months when the waters are coolest in the North-east Atlantic. They generally occurred on the western aspects of the UK and Ireland highlighting a pattern of decreasing records with increasing latitude, supporting previous suggestions that juvenile turtles arrive in these waters via the North Atlantic current systems. Similarly, the majority of the strandings and sightings of leatherback turtles ( Dermochelys coriacea, N = 1683) occurred on the western aspects of the UK and the entirety of Ireland's coastline. In contrast to hard-shell turtles, leatherback turtles were most commonly recorded in the boreal summer months with the majority of strandings being adult sized, of which there has been a recent decrease in annual records. The cause of the recent annual decreases in turtle strandings and sightings across all three species is unclear; however, changes to overall population abundance, prey availability, anthropogenic threats and variable reporting effort could all contribute. Our results provide a valuable reference point to assess species range modification due to climate change, identify possible evidence of anthropogenic threats and to assess the future trajectory of marine turtle populations in the North Atlantic.